2007
DOI: 10.1002/uog.3881
|View full text |Cite
|
Sign up to set email alerts
|

Screening for pre‐eclampsia and fetal growth restriction by uterine artery Doppler and PAPP‐A at 11–14 weeks' gestation

Abstract: Objective To assess the role of maternal demographic characteristics, uterine artery Doppler velocimetry, maternal serum pregnancy-associated plasma protein-A (PAPP-A (OR, 2.0; 95% CI, and low 0.43; 95% CI,. Increased uterine artery PI was the only independent factor in the prediction of placental abruption (OR, 8.49; 95% CI,

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

7
135
4
16

Year Published

2010
2010
2017
2017

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 177 publications
(162 citation statements)
references
References 31 publications
7
135
4
16
Order By: Relevance
“…1) El grupo estudiado entre las 11-14 semanas estuvo constituido por 55 pacientes de las cuales se seleccionaron 9 pacientes que desarrollaron PE, 10 • RCIU vs controles.…”
Section: Resultsunclassified
See 1 more Smart Citation
“…1) El grupo estudiado entre las 11-14 semanas estuvo constituido por 55 pacientes de las cuales se seleccionaron 9 pacientes que desarrollaron PE, 10 • RCIU vs controles.…”
Section: Resultsunclassified
“…Se han propuestos modelos con el fi n de predecir la PE y RCIU en edades gestacionales tempranas, pero por una parte estos presentan un bajo valor predictivo y su implementación es de alto costo económico y, por otra, no aportan intervención profi láctica alguna que permita la prevención o el retraso de la aparición de estas patologías 5,9,10 .…”
unclassified
“…pregnancy associasted plasma protein-a, PAPP-A; alfa-fetoprotein, AFP; human chorionic gonadotropin, hCG; Inhibin A) are associated with placental function and fetal growth, and their levels are altered in SGA and FGR pregnancies [56]. A low level first trimester PAPP-A should be considered a major risk factor for delivering a SGA neonate; the combination of uterine artery Doppler and maternal serum markers appears promising for improving prediction of SGA fetus, although predictive values are still poor [57][58][59]. Use of combination testing in the second trimester appears to predict adverse outcome related to placental insufficiency more effectively than first trimester screening [60].…”
Section: Screeningmentioning
confidence: 99%
“…Pilalis, et al . have reported that the predictive value of first trimester uterine artery Doppler results can be improved with the addition of maternal serum PAPP‐A, suggesting that both markers in combination may be better than either alone 18 . If the predictive value of single or combination markers in the first trimester can be improved, then therapeutic initiatives are more likely to be successful.…”
Section: The Role Of Ultrasound In Screening For Iugrmentioning
confidence: 99%